2020
DOI: 10.3390/ani10040632
|View full text |Cite
|
Sign up to set email alerts
|

Sex of Walker Influences Scent-marking Behavior of Shelter Dogs

Abstract: Interactions with humans influence the behavior and physiology of other animals, and the response can vary with sex and familiarity. Dogs in animal shelters face challenging conditions and although contact with humans typically reduces stress and behaviors associated with stress, evidence indicates that shelter dogs react differently to unfamiliar men and women. Given that some aspects of canine scent-marking behavior change under fearful conditions, we examined whether sex of an unfamiliar walker would influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Consistent with this finding relating changes in urinary behavior to stressful conditions, we previously reported that under the challenging conditions of shelter life, the percent of urinations in which mature male dogs used the raised-leg posture was 73% [26] as compared to 94-97% reported for mature male dogs living in other situations [27][28][29][30]. Further, in another study, we showed that some scent-marking behaviors exhibited during leash walks by mature shelter dogs (adults and seniors) differed when the dogs were walked by an unfamiliar man versus an unfamiliar woman [31]. When walked by an unfamiliar man, male dogs were more likely to use the juvenile lean-forward posture and urinate less frequently (another characteristic of juvenile males) than when walked by an unfamiliar woman.…”
Section: Introductionmentioning
confidence: 72%
“…Consistent with this finding relating changes in urinary behavior to stressful conditions, we previously reported that under the challenging conditions of shelter life, the percent of urinations in which mature male dogs used the raised-leg posture was 73% [26] as compared to 94-97% reported for mature male dogs living in other situations [27][28][29][30]. Further, in another study, we showed that some scent-marking behaviors exhibited during leash walks by mature shelter dogs (adults and seniors) differed when the dogs were walked by an unfamiliar man versus an unfamiliar woman [31]. When walked by an unfamiliar man, male dogs were more likely to use the juvenile lean-forward posture and urinate less frequently (another characteristic of juvenile males) than when walked by an unfamiliar woman.…”
Section: Introductionmentioning
confidence: 72%
“…Determining a dog’s personality in a dog shelter environment is a challenge not easy to deal with, because the variables that can influence the behavior of dogs are significant; in addition to the more intuitive ones, such as the availability of space, housing alone or with other dogs, the frequency of contact with human beings, the frequency of going out from the cage and so on [ 32 ]; for example, McGuire et al [ 33 ] found that, in a shelter, even the sex of the walker influences dog’s elimination behavior. Furthermore, the structure is not designed to perform behavioral test batteries properly.…”
Section: Discussionmentioning
confidence: 99%
“…Although wolves use feces for territorial marking [ 70 ], defecation is thought to play a less important role in communication in dogs [ 69 ]. However, when walked by an unfamiliar man, shelter dogs defecated less than when walked by an unfamiliar female [ 76 ].…”
Section: Olfactory Behaviormentioning
confidence: 99%
“…Jezierski et al identified that individual elements such as style and time of sniffing can influence the results of a dog’s olfactory work [ 78 ]. Other factors such as the effects of the dog’s routine, the use of cues other than olfactory ones (visual), and the non-verbal communication between handler and dog have also been mentioned [ 39 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 ].…”
Section: Limitations In Canine Detection—a Critical Assessmentmentioning
confidence: 99%